The Morphosyntax Of English Deverbal Noun In The Straits Times Website - Ayu Indah Maha Dewi, I Gusti; Qomariana, Yana (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p26, 2018)
The title of this study is “The Morphosyntax of English Deverbal Noun in The Straits Times Website”. This study was conducted in order to find out and analyze the forms and syntactic functions of deverbal noun in The Straits Times website. There were two theories used in this study. The first was the theory proposed by Plag (2002) used to analyze the forms of deverbal noun and the second theory proposed by Quirk (1985) used to analyze the syntactic functions. The data were taken from the lifestyle articles in Straits Times website. The data were collected by documentation method. The collected data were analyzed by using the qualitative method. This study applied formal and informal methods to present the analysis. The result of this study showed that among nominal suffixes forming nouns from verbs stated by Plag, there are seven suffixes found in the data; they are suffix /-age/, /-ance/, /-ant/, /-er/, /-ing/, /-ion/ and /-ment/. Besides, in relation to the syntactic functions, there are four syntactic functions found in the data, they are as part of subject, object, subject complement and object complement functions.